Synthesis of 3,4,5-trisubstituted isoxazoles in water via a [3 + 2]-cycloaddition of nitrile oxides and 1,3-diketones, β-ketoesters, or β-ketoamides - Hossain, Md Imran; Khan, Md Imdadul H.; Kim, Seong Jong; Le, Hoang V. (Beilstein Journal of Organic Chemistry, 2022)
Herein we report a method for the synthesis of 3,4,5-trisubstituted isoxazoles in water under mild basic conditions at room temperature via a [3 + 2]-cycloaddition of nitrile oxides and 1,3-diketones, β-ketoesters, or β-ketoamides. We optimized the reaction conditions to control the selectivity of the production of isoxazoles and circumvent other competing reactions, such as O-imidoylation or hetero [3 + 2]-cycloaddition. The reaction happens fast in water and completes within 1–2 hours, which provides an environmentally friendly access to 3,4,5-trisubstituted isoxazoles, an important class of structures found in numerous bioactive natural products and pharmaceuticals. Additionally, we optimized the reaction conditions to produce trifluoromethyl-substituted isoxazoles, a prevalent scaffold in biomedical research and drug discovery programs. We also proposed a plausible mechanism for the selectivity of the [3 + 2]-cycloaddition reaction to produce 3,4,5-trisubstituted isoxazoles. Not to be overlooked are our optimized reaction conditions for the dimerization of hydroximoyl chlorides to form furoxans also known as 1,2,5-oxadiazole 2-oxides, a class of structures with important biological activities due to their unique electronic nature and coordination ability.
Keywords: environmentally friendly; furoxans; 1,2,5-oxadiazole 2-oxides; trifluoromethyl-substituted isoxazoles; 3,4,5-trisubstituted isoxazoles